2004
DOI: 10.1161/01.atv.0000143386.26399.84
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Experimental Aortic Aneurysm Formation

Abstract: Objective-It is hypothesized that a male predominance, similar to that in humans, persists in a rodent model of experimental abdominal aortic aneurysm (AAA) via alterations in matrix metalloproteinases (MMPs). Methods and Results-Group I experiments were as follows: elastase perfusion of the infrarenal aorta was performed in male (M) and female (F) rats. At 14 days, aortas were harvested for immunohistochemistry, real-time polymerase chain reaction (PCR), and zymography. Group II experiments were the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
2
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(163 citation statements)
references
References 42 publications
4
150
2
7
Order By: Relevance
“…Male rats treated with 17b-estradiol had smaller aortic diameter, less macrophage infiltration, and elastin fragmentation as well as lower levels of MMP9 mRNA compared with the sham group. 64 The protective effects of estrogens were confirmed by other studies. 69,70 Additionally, Martin-McNultry et al 71 demonstrated that infusion of AngII induced AAA in 90% of Apoe À/À mice, whereas with 17b-estradiol treatment, only 42% of mice developed AAAs.…”
Section: Exogenous Estrogens In Aaasupporting
confidence: 58%
See 1 more Smart Citation
“…Male rats treated with 17b-estradiol had smaller aortic diameter, less macrophage infiltration, and elastin fragmentation as well as lower levels of MMP9 mRNA compared with the sham group. 64 The protective effects of estrogens were confirmed by other studies. 69,70 Additionally, Martin-McNultry et al 71 demonstrated that infusion of AngII induced AAA in 90% of Apoe À/À mice, whereas with 17b-estradiol treatment, only 42% of mice developed AAAs.…”
Section: Exogenous Estrogens In Aaasupporting
confidence: 58%
“…This apparent female protection was mediated by inhibitory effect of estradiol on the aortic wall macrophage infiltration and secretion of MMP9. 64 They also noticed that estrogen-related resistant phenotype was lost after transplantation of the female aorta into male rats. Moreover, the male and female aortas had nearly identical aortic structure before any intervention, suggesting a postinjury action of estrogen.…”
Section: Sex Differences In Aaa Animal Models the Role Of Endogenous mentioning
confidence: 99%
“…Protein concentrations were determined with BCA Protein Assay. Reverse Zymography was modified according to previous publications (3,4). Briefly, equal amounts of proteins (30 μg/lane) were loaded onto SDS-polyacrylamide gels (12%), which copolymerized with supernatant of smooth muscle cells and 1% gelatin.…”
Section: Reverse Gelatin Zymographymentioning
confidence: 99%
“…Male patients affected by type 1 diabetes mellitus have increased urinary MMP-9 (29). Gender difference in MMP-9 concentration was also shown in experimental aortic aneurysm (30) and rat aortic smooth muscle cells (31). Interestingly, other diseases may show gender differences in the MMP-9 -1562/TIMP-1 372 polymorphisms (32).…”
Section: Discussionmentioning
confidence: 93%